Assessment of the Level of Motivation of Academic Achievement, Professional Orientation and Future Perceptions of Students of Physical Education Faculties in the Middle Euphrates Universities - Ayman Hani Abed Al-Gburi (Journal of Global Pharma Technology, 2016)
The Study ObjectivesEstablish standard levels of motivation for academic achievement, professional orientation and future perceptions of students of physical education faculties in the middle Euphrates universities.To identify the drivers of academic achievement, professional orientation and future perceptions of students of physical Education colleges at the middle Euphrates universities.To identify the level of motivation of academic achievement, professional orientation and future perceptions of students of physical education faculties in the middle Euphrates universities.Researchers used the survey curriculum to identify the drivers of academic achievement, professional orientation, future perceptions and student assessment according to these variables, and the research community included the students of the fourth stage in the faculties of Physical Education and Sports sciences at the Middle Euphrates universities, after which it was applied Metrics for the purpose of conducting the assessment, and using the appropriate statistical means in order to process data using the statistical pouch (SPSS).In the light of the results of the present research, and of the interpretations that have been followed, we can draw some conclusions, the most important of which are the following:Standard standards of motivation for academic achievement, professional orientation and future perceptions have been established for students of Physical Education Colleges and Sports sciences at the Middle Euphrates universities.Students of the faculties of Physical Education and Sports sciences at the Middle Euphrates universities have an average level of motivation for academic achievement, professional orientation and future perceptions.There is a potential for developing the motivation for academic achievement, professional orientation and future perceptions of students of physical Education Colleges and Sports sciences at the Middle Euphrates universities.In the light of the findings and conclusions of the research, the current research has reached the most important recommendations, as follows:To take advantage of the benchmarks of academic achievement, professional orientation and future perceptions that researchers have applied and set standards for them to detect these variables for students of physical Education Colleges and Sports Sciences in Iraq.Use of standards in educational and psychological guidance to develop the motivation of academic achievement, professional orientation and future perceptions.The need to provide specific lectures to students during educational and teaching units by a psychologist and a psychologist.Keywords: Assessment, Academic achievement, Professional orientation and future perceptions.